Un système expert d'aide à la décision pour le développement durable de Djerba - Ghribi, Abdelhamid; Buchmann, Ernst; Khattali, Houcine (Municipalité de Djerba Houmt-Souk, 2007)
Keywords: Développement durable – Djerba

Oasis Settlement in Oman Pilot Study 1999 - 2000 - Ibrahim, Moawiyah; Mershen, Birgit; Gaube, Heinz; Ribbeck, Eckhart; Gangler, Anette; Buerkert, Andreas; Häser, Jutta (Universität Stuttgart, 2001)

Tafilelte Tajdite - Nouh, Ahmed (2007)
Keywords: Urbanisme – Mzab

Islam and the particularities of the Ibadi denomination - Hoffmann, Anne; Dittrich, Priska (Universität Kassel, 2007)
A group of 29 forestry and agriculture students and faculty from the Universities of Kassel and Goettingen participated in a joint study tour to Oman from 24th of February to 10th of March 2007. The excursion´s aim was to gain first-hand impressions and knowledge on traditional and modern land- and resource use systems in Oman. Besides this thematic focus, we also tried to learn about the culture and way of living of the people in Oman. Therefore we are especially happy that we had the opportunity to exchange thoughts with Omani students from Sultan Qaboos University who joined part of our tour. This homepage is intended to present the topics that the study tour delt with as well as give some picture impressions from our two-week journey through Oman.
Keywords: Récits de voyage – Oman

The right to freedom of opinion and expression - Ligabo, Amebyi (Nations Unies, 2006)
On 3 February 2006, the Special Rapporteur, together with the Independent Expert on Minority Issues, the Special Rapporteur on contemporary forms of racism, racial discrimination, xenophobia and related intolerance, and the Special Rapporteur on the situation of human rights and fundamental freedoms of indigenous sent a letter of allegation concerning information received regarding discrimination toward Berbers, particularly on the existence of discriminatory legislations toward the Berber culture and identity, such as the law number 24 of the year 1369 w.r. (1991). Reportedly, the said laws prevent people from using any other language than Arabic in the country and also forbid literature and writings which is not in Arabic, and therefore, the use of the Berber language. It is also alleged that it is forbidden to use names of Berber origin to name children. It has been also alleged that the Libyan government deliberately withholds the development of regions with Berber communities. As an example, the only hospital in the region of Zouara, which was closed in the 1980’s, has not been reopened and that there is no hospital in the region. Similarly, it has been alleged that the water projects in the country have deliberately excluded the regions of Nefoussa and Zouara. The information also alledged that the Libyan education system and school books do not take into account the Berber component in Libya’s geography, history and culture. Allegations also report the harassment and ill-treatment of persons working for the defence of the Berber community, culture and identity.
Keywords: Vie politique – Djebel Nefousa

Co-opting Identity: The manipulation of Berberism, the frustration of democratisation, and the generation of violence in Algeria - Roberts, Hugh (London School of Economics and Political Science, 2001)
Keywords: Conflits – Mzab

A Study of the Formative Factors of the Free Trade Agreement Between Oman and the United States - Smith, Gregory (School for International Training, 2006)
Keywords: Relations – Oman – Etats-Unis

Etude d'impact sur l'environnement du projet de la construction du collège secondaire à Ajim Djerba - Audit Environnemental L' (Gouvernorat de Médenine, 2003)
Keywords: Architecture – Djerba

Maison de Djerba (Euromed Heritage, 2001)
Keywords: Architecture – Djerba

The emergence of post-traditional Oman - Peterson, John E. (University of Durham, 2005)
Keywords: Vie politique – Oman – 1970-2020

Emerging Identities in Colonial Tunisia: "Alliancist" and Zionist Representations in Tunis prior to World War I - Land, Joy (University of Connecticut, 2009)
Keywords: Judaïsme – Djerba

A Lion in the Path of Oman's Nationalization: Insurgency in Oman from the 1950s through the 1970s Examined through Social Movement Theory: - Howk, Jason (Defense Technical Information Center, 2008)
Keywords: Vie politique – Oman – 1932-1970

Examen des rapports présentés par les États parties conformément aux articles 16 et 17 du pacte : Jamahiriya arabe libyenne : Observations finales du comité des droits économiques, sociaux et culturels (Conseil économique et social, 2006)
Keywords: Vie politique – Djebel Nefousa

Rembrandt in Oman - Schmierer, Richard J. (US Embassy, 2009)
Keywords: Vie culturelle – Oman

Oman: Jewish engagement - Schmierer, Richard J. (US Embassy, 2009)
Keywords: Judaïsme – Oman

Rapport général sur la situation des droits humains des Imazighen de Libye (Tawalt, 2007)
Keywords: Vie politique – Djebel Nefousa

Ghardaia, Ideological and Cultural Oasis - Pearce, David D. (US Embassy, 2009)
Keywords: Moeurs et coutumes – Mzab

Politics Rattle the Tunisian-American Chamber of Commerce - Godek, Robert F. (US Embassy, 2009)
Keywords: Barouni; Mohamed Moncef

Ambassador Visits Jewish Community in Djerba - Godek, Robert F. (US Embassy, 2009)
Keywords: Judaïsme – Djerba

Annual Jewish Pilgrimage Proceeds Peacefully - Godek, Robert F. (US Embassy, 2008)
Keywords: Judaïsme – Djerba

Southern Tunisia's Encomium to Ben Ali - Godek, Robert F. (US Embassy, 2007)
Keywords: Judaïsme – Djerba

Tunisian-American Chamber elects new board - Godek, Robert F. (US Embassy, 2007)
Keywords: Barouni; Mohamed Moncef

Tunisian reation to Lebanon/Israel/Gaza - Godek, Robert F. (US Embassy, 2006)
Keywords: Barouni; Mohamed Moncef

Jewish Pilgrimage to Djerba, a Tunisian Success Story - Hudson, William (US Embassy, 2006)
Keywords: Judaïsme – Djerba

End of the Road, the Last Imam of Oman Dies, But... - Hurtado, L. Victor (US Embassy, 2009)
Keywords: Hinai; Ghalib bin Ali al- (1913-2009)

Kudos and follow-up questions for reporting on imam Ghalib's death - Pitterle, Elissa G. (Secretary State, 2006)
Keywords: Vie politique – Oman – 1970-2020

Plan de sauvegarde et de promotion du ksar de Berriane et son intégration avec le centre ville : Phase 1 analyse et diagnostic - Urbat (Direction de l'urbanisme et de la construction, 2000)
Keywords: Urbanisme – Mzab

Kadhafi s'intéresse au mouvement amazigh - Abrouri (Coordination des Berbères de France, 2005)
Keywords: Vie politique – Djebel Nefousa

Voyage d'étude à Midoun, Djerba, Tunisie, du 12 au 18 mars 2000 - Ecole d'Architecture Languedoc-Roussillon (EA Languedoc-Roussillon, 2000)
Keywords: Architecture – Djerba

La guerre du Dhofar, 1965-1976: un modèle de contre-rébellion - Morin, Tony (Centre de doctrine d'emploi des forces, 2009)
La guerre du Dhofar se déroulant dans le sultanant d'Oman et engageant des troupes britanniques entre 1965 et 1976 illustre une réussite peu connue de contre-rébellion, car menée dans la discrétion et intégrant complètement actions civiles et militaires.
Keywords: Dhofar

Le débat sur l'identité nationale en Oman : rapport de consultance rédigé pour la Délégation aux affaires stratégiques (Ministère de la Défense, 2004)
Ce travail s'attache à mettre en évidence, dans un contexte historique, les ressorts de la remarquable stabilité du sultanat d'Oman depuis 1970, date à laquelle le sultan Qabous Bin Sa'id a accédé au trône. Héritier d'un territoire sans Etat, le nouveau souverain, porté au pouvoir par les britanniques, a su construire durant son règne une identité nationale omanaise moderne et associer l'image de sa personne au développement économique et social sans précédent impulsé par l'Etat et la rente pétrolière. Pourtant, loin de se révéler en rupture avec l'histoire moderne d'Oman, comme le suggère l'historiographie officielle, le règne de Qabous s'inscrit par de nombreux aspects dans la continuité du règne de son père, Sa'id (1932-1970). En mêlant cooptation des élites traditionnelles et coercition à l'égard des foyers de contre-pouvoirs, le souverain a rallié à son autorité l'ensemble des forces sociopolitiques susceptibles de le gêner. La dernière décennie a [vu] néanmoins de nombreux bouleversements se produire dans la société omanaise, avec l'apparition de défis politiques et sociaux à même de remettre en cause la stabilité en place : ralentissement de la production pétrolière, revendications politiques inédites, nécessaire nationalisation des emplois, etc. L'une des principales évolutions consiste en une repolarisation de la société autour d'identités infra-nationales - ethnolinguistiques, régionales - anciennes ou nouvelles.
Keywords: Vie politique – Oman – 1970-2020

Étude de développement agricole intégré de l’île de Djerba - Sghaier, Mongi (Institut des Régions Arides, 2000)
[Ministère de l’Agriculture, 1998, Étude de développement agricole intégré de l’île de Djerba, CRDA de Médenine, BERA, Tunis.] ?
Keywords: Agriculture – Djerba

Schéma Directeur d’Aménagement de Djerba-Zarzis - Chabbi, Morched (Comete Engineering, 2000)
pour le compte de la Direction Générale de l’Aménagement du Territoire - Ministère de l’Environnement et de l’Aménagement du Territoire
Keywords: Urbanisme – Djerba

Personal Narratives as a Peacebuilding Tool: A Study of Djerbien Jewish and Muslim Co-existence - Robana, Aida (School for International Training, 2005)
Throughout my life, my Djerbien grandmothers emphasized the importance of storytelling and of recording the oral history of their small Tunisian island. Djerba is unique in many ways, not least of which is its thriving community of Muslims and Jews who have lived together in peace for centuries. Particularly considering the deep-seeded conflicts between people of these two religions in other parts of the world, I wanted to explore how Djerbiens have used narratives to create and maintain a culture of co-existence. I engaged in in-depth interviews with eight residents of El Hara Esseghira and El Hara Kebira, two Djerbien communities where Muslims and Jews have lived together for over a millennium. Three major themes were revealed in the course of the research: kinship, communal relations, and social identity. The data collected from in-depth interviews, informal interviews, and observation help to explain the co-existence that is prevalent on the island, and can serve as inspiration to diverse communities throughout the world struggling to co-exist. This study will also aid in preserving the richness that exists within Djerbien identity and culture while demonstrating how narratives contribute to a culture of co-existence within their community.
Keywords: Judaïsme – Djerba

Projet de recharge artificielle de la nappe de Jerba à partir des eaux usées traitées de la STEP d’Aghir - Egs Engineering (2006)

Dossiers technique et administratif pour la création d’aires spécialement protégées dans l’île de Djerba - Assidje (Association pour la Sauvegarde de l’île de Djerba, 2000)

étude générale pour la protection du littoral tunisien contre l’érosion marine - littoral nord-est de Jerba. Avant-projet sommaire - Apal (Studi-Sogreah-groupe canadien, 2001)
Keywords: Littoraux – Djerba

Gestion de zone sensible. La presqu’île de Bin Ouediane - Apal (Comete Engineering, 2000)
Keywords: Littoraux – Djerba

La génétique des populations de l’île de Jerba (Tunisie): une recherche en cours - Mourali, Soufia; Heyer, Evelyne (École des Hautes Etudes en Sciences Sociales, 2001)
Keywords: Génétique – Djerba